Implementasi Model SAVI (Somatis, Auditori, Visual, dan Intelektual) dalam Pembelajaran PAI dan BP pada Anak Tunagrahita di SLB C-C1 Yakut Purwokerto - Nurfadilah, Syafa; Toifur (Jurnal Pendidikan Agama Islam, 2025)
Teaching Islamic Religious Education and Ethics to children with intellectual disabilities requires innovation in the use of learning models that can be adapted to the limitations of children with intellectual disabilities in understanding material and their abstract thinking abilities. The SAVI (Somatic, Auditory, Visual, and Intellectual) model is one solution because it combines the use of all five senses, body movements, and thinking activities to improve student understanding. This study aims to describe the implementation of the SAVI model in PAI and BP learning for children with intellectual disabilities in grade VII at SLB C-C1 Yakut Purwokerto, with the research subjects being PAI teachers, students, and the school principal. This study is a field study with a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the SAVI model has been carried out in accordance with the concept of the SAVI learning model and adapted to the characteristics of children with intellectual disabilities. Learning takes place through four stages: preparation, presentation, training, and presentation of results. Teachers also use a combination of several teaching methods and media that support somatic, auditory, visual, and intellectual elements, making the learning process more active, enjoyable, and easy to understand, and helping students achieve learning objectives optimally